The Effectiveness of Group Guidance Services through Modeling Techniques by Applying the Tabligh Nature of Rasulullah SAW. to Increase the Self-Confidence of Class VII Students at MTSn 2 Medan - Puspita, Sholihah; Suryani, Ira; Syarqawi, Ahmad (Universitas Muhammadiyah Sumatera Utara (UMSU), 2024)
Research that has been conducted with the title“The Effectiveness of Group Guidance Services through Modeling Techniques withApplying the Tabligh Nature of the Prophet Muhammad Saw. to Increase Self-Confidence Class VII students at MTsN 2 Medan” which is motivated by the phenomenon of field findingsshows that there are students who experience low self-confidencelow self-confidence such as an attitude that is not brave and anxious students when presenting the results of a discussion in front of the class and not daring to appeardiscussion in front of the class and not daring to perform murojo'ah activities. The purpose ofThe objectives of this study are (1) to determine the description of students' self-confidence in class VII at MTsN 2 Medan.class VII students at MTsN 2 Medan. (2) to find out the effectiveness of group guidance services through modeling techniques by applying the tabligh nature of Rasulullah Saw. to increase the confidence of seventh grade students at MTsN 2 Medan. This research using a quantitative approach with a pretest - posttest control group design. group design. The results showed that: (1) Increased self-confidence of students in class VII H MTsN 2 Medan. Before the intervention, 70% of students were in the medium category and 30% in the low category. After the intervention, 50% of students were in the medium category and 50% in the high category. (2) There is an effectiveness of group guidance services modeling techniques by applying the tabligh nature of Rasulullah Saw. in increasing student confidence. A significant difference can be seen between the pre-test and post-test results with a sig value. (2 tailed) of 0.005 0.05, which means that there is a significant effect before the intervention (pre-test) and after the intervention (post-test) on students' self-confidence.